TRANSFORMATION OF MSME PROMOTIONAL STRATEGIES THROUGH SOCIAL MEDIA IN THE DIGITAL ERA: A STUDY OF MSMES IN BEKASI (POLITEKNIK LP3I JAKARTA, 2026)
The rapid growth of digital technology has changed the way micro, small, and medium enterprises (MSMEs) promote their products and communicate with customers. Social media, which was initially used mainly for communication, has now become an important marketing platform that allows MSMEs to build brand awareness, interact with customers, reach wider markets, and support business growth. This study aims to examine how promotional strategies among MSMEs have changed through the use of social media and to identify the factors that support successful digital marketing, particularly among MSMEs in Bekasi, Indonesia. This study uses a qualitative descriptive approach based on a structured review of national and international journal articles indexed in SINTA, Scopus, and Web of Science. The analysis shows that the transformation of MSME promotion generally develops gradually, beginning with conventional promotion, followed by a basic digital presence, content-based promotion, interactive social media marketing, and more integrated digital promotion. The success of this transformation is influenced by digital literacy, technological readiness, organizational capability, innovation, customer engagement, and market competition. Social media also gives MSMEs the opportunity to build closer relationships with customers and encourage electronic word of mouth. For MSMEs in Bekasi, social media provides a practical opportunity to expand their market and strengthen their competitive position. However, meaningful digital transformation requires more than simply having social media accounts. MSMEs need consistent, relevant, interactive, and measurable promotional strategies that are closely connected to customer needs and business objectives.